Statement in regard to the Minister of Health's White Paper on the establishment of "A National Health Service." (1944)
1944 1944 1940s 18 pages (ii) The whole T.U. movement should take a firm stand and demand a definite announcement and undertaking from the Minister, as representing the Government, that freedom of Association and Trade Union organisation is to be a guaranteed right of every Health Worker in any section of the new Health Scheme, whether engaged in Home Nursing, or traetment [treatment] in clinics or Hospitals and Insitutions of every type, without any pressure or influence from executives. That all employees be granted the same privilege of organisational choice as is conceded to the medical professional workers. (B) THE CENTRAL MEDICAL BOARD. As its name impies [implies] this is a special body, with executive and administrative duties acting on behalf of the Minister as the employer of that particular group of the medical professional workers under contract in the Scheme, either recognised as members 'of the General Practitioners Service', whether working in Health Centres; in clincs [clinics]; in group practices or in 'seperate practices' as mainly obtain at present or as consultants. (this is doubtful). It is a body for dealing with contracting groups of the medical workers 'in the day-to-day working' of the scheme, and does not include consultants (apparently even if working in Health Sentres [Centres]) or administrative offices, or any of the other Health Workers in the scheme. Presumably, these other workers will be under contract with Local Authorities, or ''ad hoc" bodies, but the White Paper is obscure on these points. Clearly this body should be a Central Health Board, with executive duties covering ALL the health workers in any group or part of the the scheme. The deliberate vagueness of the powers of the Board is to cover the Minister's administrative difficulties in dealing with Medical Consultant Staff working in Health Centres or helping general practitioners in domiciliary visits in consultation. It is proved that these consultants should normally be attached to Hospitals and Institutions, and as the duel system of Medical Institutions is to be preserved, special contractuel [contractual] obligations will have to be devised for the medical consultants in the service. This added difficulty is the result of a compromise medical policy. The establishment of this 'special executive body' is dealt with in that part of the White Paper (Chapt.V)., explaining the policy on the General Practitioners' service. The Board is recognised under the general direction of the Minister, but its officers will be practically medical civil servants, permanently appointed, whether working full-time or part-time really acting as the employer for the Government of the general practitioner under contract. The details of the medical contract for public service has yet to be negotiated and settled, but the doctor will be expected to give in his personal service "all normal professional advice and service within his proper competence" to his patients, and to comply with the approved area plan for medical services and to observe the 'reasonable, conditions centrally determined with the profession, respecting CERTIFICATION and other matters." Machinery for hearing of complaints against doctors by patients, and for the general kind of disciplinary and appeal procedure will be formed. No doctor will be able to practice in any area, in any contract for public service, without the consent of the Board. The problems affecting the doctor's future or enforced termination of a contract are lightly skimmed over. National Health Insurance Committees now existing are marked down for dissolution. Private medical practice remains undisturbed at any doctor's individual risk of success outside the contractual public service. The public service, however, will be supervised to secure proper distribution of doctors per area. Health Centre appointments for young doctors will be handled by the Board. So much for the two Central and Main Committees, undemocratic in election, undemocratic in control. The danger which we envisage is that owing to the obscurity of the whole scheme, particularly in its local administration and control, plus the duel systems operating and maintained, these two Boards may by a gradual process take over, or have added to them by a Minister who uses the easiest expedient as a 'way out', considerbly [considerably] greater powers. Conflict is 7. 292/847/2/43